Mitochondria to plasma membrane redox signaling is essential for fatty acid β-oxidation-driven insulin secretion - Jabůrek, Martin; Klöppel, Eduardo; Průchová, Pavla; Mozheitova, Oleksandra; Tauber, Jan; Engstová, Hana; Ježek, Petr (Redox biology, 2024)
We asked whether acute redox signaling from mitochondria exists concomitantly to fatty acid- (FA-) stimulated insulin secretion (FASIS) at low glucose by pancreatic β-cells. We show that FA β-oxidation produces superoxide/H2O2, providing: i) mitochondria-to-plasma-membrane redox signaling, closing KATP-channels synergically with elevated ATP (substituting NADPH-oxidase-4-mediated H2O2-signaling upon glucose-stimulated insulin secretion); ii) activation of redox-sensitive phospholipase iPLA2γ/PNPLA8, cleaving mitochondrial FAs, enabling metabotropic GPR40 receptors to amplify insulin secretion (IS). At fasting glucose, palmitic acid stimulated IS in wt mice; palmitic, stearic, lauric, oleic, linoleic, and hexanoic acids also in perifused pancreatic islets (PIs), with suppressed 1st phases in iPLA2γ/PNPLA8-knockout mice/PIs. Extracellular/cytosolic H2O2-monitoring indicated knockout-independent redox signals, blocked by mitochondrial antioxidant SkQ1, etomoxir, CPT1 silencing, and catalase overexpression, all inhibiting FASIS, keeping ATP-sensitive K+-channels open, and diminishing cytosolic [Ca2+]-oscillations. FASIS in mice was a postprandially delayed physiological event. Redox signals of FA β-oxidation are thus documented, reaching the plasma membrane, essentially co-stimulating IS.
Keywords: Insulin; Receptors, G-Protein-Coupled; GPR40; Mitochondria; Glucose; Mice, Knockout; inzulin; fosfolipasy A2, skupina VI; mastné kyseliny; signální transdukce; peroxid vodíku; glukosa; Fatty Acids; Hydrogen Peroxide; Fatty acid-stimulated insulin secretion; Signal Transduction; myši knockoutované; oxidace-redukce; Cell Membrane; Redox signaling; Redox-activated phospholipase iPLA2γ; Animals; sekrece inzulinu; zvířata; beta-buňky; buněčná membrána; receptory spřažené s G-proteiny; myši; Insulin-Secreting Cells; Pancreatic β-cells; Oxidation-Reduction; Mice; Mitochondrial fatty acids; Insulin Secretion; mitochondrie; Group VI Phospholipases A2